PENGARUH BRAND IMAGE, KUALITAS PELAYANAN, DAN KEBERAGAMAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN MELALUI MINAT BELI SEBAGAI VARIABEL INTERVENING PADA TOKO ROTI PERMATA BAKERY SITUBONDO - Miftahur Rasyid; Randika Fandiyanto; Siti Soeliha (Fakultas Ekonomi dan Bisnis, 2025)
This study aims to analyze the effect of brand image, service quality, and product diversity on purchase decisions, with purchase intention as an intervening variable among customers of Permata Bakery Situbondo. This research uses a quantitative approach with a survey method, involving 99 respondents selected through purposive sampling. Data analysis was conducted using Partial Least Square - Structural Equation Modeling (PLS-SEM). The results show that brand image, service quality, and product diversity have a significant positive effect on purchase intention. Furthermore, purchase intention significantly influences purchase decisions. In addition, brand image and product diversity have a significant effect on purchase decisions both directly and indirectly through purchase intention as a mediating variable. These findings highlight the importance of strengthening brand image, improving service quality, and providing product variety to enhance consumers’ purchase decisions.